PENERAPAN KEBIJAKAN GENERAL AGREEMENT ON TRADE IN SERVICE DALAM PERKEMBANGAN HUKUM PARIWISATA - Sudini, Luh Putu; Wiryani, Made; Laksmi, A A Rai Sita (Jurnal Hukum Magnum Opus, 2021)
AbstractPaying attention to the development of the tourism sector in the Bali Province which has ups and downs or in other words the tourism sector in Bali due to political and social conditions has caused domestic and foreign tourist visits to tourism in Bali Province to increase and sometimes decrease, such as during the Bali Bombing I and The Bali Bombing II, causing the presence of domestic and foreign tourist visits to Bali Province Tourism to decline, even severely slumped. In this study, trying to examine the existence of the General Agreement Trade on Tariff (GATS) policy on the development of tourism in Bali Province. The problem taken is how to implement the General Agreement on Trade in Service (GATS) policy on tourism visits in Bali Province? and what is the impact of tourism policy in Bali Province after the ratification of the General Agreement on Trade in Service (GATS)? This research is a normative legal research. The implementation of the GATS policy by the Government of Indonesia through the provisions of Law no. 10-2009 including the policy on the characteristics of tourists visiting Bali, it appears that the implementation of the Bali Province policy on tourism is able to provide satisfaction for tourists visiting Bali so that tourists will repeat their arrival to Bali Province. After the GATS ratification, the tourism policy in Bali Province and regencies / cities in Bali had an impact on the number of tourist visits, especially domestic or domestic tourists, experienced a significant increase in 2016-2017, namely 8,643,680 in 2016 to 8,735,633 in 2017, so that there was an increase of 1.06%. In addition, the ratification of the GATS policy by the Government of Indonesia has had a positive impact on the formation of tourist objects that the Bali Provincial Government can offer to tourists visiting Bali Province, and the tourism objects offered can increase tourist visits to Bali Province.Keywords: application; GATS policy; tourismAbstrakMemperhatikan perkembangan bidang pariwisata di wilayah Provinsi Bali yang jatuh bangun atau dengan kata lain sektor pariwisata di Bali akibat kondisi politik dan sosial menyebabkan kunjungan wisatawan domestik dan manca Negara terhadap pariwisata di Provinsi Bali bisa meningkat dan kadang kala menurun seperti saat ada kejadian Bom Bali I dan Bom Bali II, menyebabkan keberadaan kunjungan wisatawan domestik dan luar negeri terhadap Pariwisata Provinsi Bali menjadi menurun jatuh bahkan sangat terpuruk. Dalam penelitian ini, mencoba meneliti berkaitan dengan keberadaan kebijakan General Agreement Trade on Tariff (GATS) terhadap perkembangan Pariwisata di Provinsi Bali. Permasalahan yang diambil yaitu bagaimana penerapan kebijakan General Agreement on Trade in Service (GATS) terhadap kunjungan pariwisata di Provinsi Bali? dan bagaimana dampak kebijakan pariwisata di Provinsi Bali setelah ratifikasi General Agreement on Trade in Service (GATS)? Penelitian ini merupakan penelitian hukum normati. Penerapan kebijakan GATS oleh Pemerintah Indonesia melalui ketentuan UU No. 10-2009 termasuk juga kebijakan terhadap karakteristik wisatawan yang berkunjung Ke Bali, tampak bahwa penerapan kebijakan Provinsi Bali bidang pariwisata mampu memberikan kepuasan bagi wisatawan yang berkunjung ke Bali sehingga wisatawan akan mengulangi kedatangannya ke Provinsi Bali. Kebijakan Pariwisata di Provinsi Bali maupun kabupaten/kota di seluruh Bali, setelah ratifikasi GATS berdampak terhadap jumlah kunjungan wisatawan utamanya wisatawan nusantara atau dalam negeri, mengalami peningkatan signifikan pada tahun 2016- 2017 yakni 8.643.680 tahun 2016  menjadi 8.735.633 tahun 2017, sehingga terjadi peningkatan sebesar 1,06%. Selain itu, ratifikasi kebijakan GATS oleh Pemerintah Indonesia, berdampak positip terhadap terbentuknya objek-objek wisata yang mampu ditawarkan oleh Pemerintah Provinsi Bali kepada para wisatawan yang berkunjung ke Provinsi Bali, dan objek pariwisata yang ditawarkan dapat meningkatkan kunjungan wisatawan ke Provinsi Bali.